Invasive freshwater jellyfish has become established in artificial impoundments of Anatolian Peninsula - Nurçin Killi; Sadi Aksu; Sera Övgü Kabadayı Yıldırım; Sercan Başkurt; Özgür Emiroğlu; Ayşe Pınar Öztopçu Vatan; Irmak Kurtul; Serdar Aksan; Ali Serhan Tarkan (Turkish Journal of Bioscience and Collections)
Objective: A freshwater jellyfish Craspedacusta sowerbii is frequently found in disturbed or artificial bodies of water, e.g. quarry ponds and gravel pits, reservoirs, aquaria and even wastewater treatment facilities, it can also thrive in natural lentic and lotic habitats. In the present study, we present two new records for C. sowerbii which is non-native to Turkey and provide the distribution data of the species in Turkey and Europe. Materials and Methods: The jellyfish samples were obtained from two localities by fishing nets and hand net. Temperature, pH and dissolved oxygen values of the two sampling areas were measured in both of the sampling areas. Results: Non-native freshwater jellyfish Craspedacusta sowerbii is recorded from two different localities namely Akdeğirmen Reservoir (Afyon) and Atabey Reservoir (Isparta) in Turkey. Twelve individuals and two individuals of C. sowerbii were sampled in Akdeğirmen Reservoir (Afyon) and Atabey Reservoir (Isparta), respectively. Temperature, pH and dissolved oxygen values of the two sampling areas were 18.7ºC, 7.9, 6.34 mg/l in Akdeğirmen Reservoir, and 10.9ºC, 7.94, 9.36 mg/l in Atabey Reservoir. Conclusion: Many studies suggested that it could tolerate a wide range of temperatures from 10°C to 28°C and spread by fish stocking activities as well as by migratory birds in Turkey. It may have been possible for Craspedacusta sowerbii to be introduced to Akdeğirmen Reservoir where there are many actively moving cormorants colonies. Also, spread of this species may have been facilitated by fish stocking activities in Turkish inland waters.